Legal Implications of Interfaith Marriage on Inheritance Rights and Child Status in the Perspective of Islamic Law and Civil Law - Shalihah , Shalihah; Karima , Nadia Rif’atul; Al Amruzi, M. Fahmi (JOURNAL OF ISLAMIC AND LAW STUDIES, 2025)
Interfaith marriage remains a controversial issue within Indonesia's pluralistic legal system, which recognizes both religious and civil legal frameworks. This paper examines the legal implications of interfaith marriage concerning inheritance rights and the legal status of children from the perspectives of Islamic law and civil law. Employing a normative legal research method and a literature-based approach, the study analyzes statutory regulations, judicial decisions, and legal doctrines relevant to the rights of interfaith families. The findings reveal that in Islamic law, religious differences serve as a barrier to inheritance and affect the legitimacy of the child’s legal status. In contrast, civil law provides broader protection, recognizing inheritance rights and child status without religious discrimination. Although legal reconciliation efforts—such as the doctrine of wasiat wajibah (compulsory bequest) and recognition of biological paternity—offer partial solutions, the lack of regulatory harmony continues to produce uncertainty and legal challenges. Therefore, harmonizing existing regulations is essential to ensure justice and legal certainty for interfaith families in Indonesia.